The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1111/jace.19497
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles as a new sintering additive for the fabrication of YAG:Ce optical luminescent ceramics

Alexander A. Kravtsov,
Evgeniy V. Medyanik,
Vitaly A. Tarala
et al.

Abstract: In this study, silver nanoparticles (NPs) were considered for the first time as a sintering additive in the manufacture of YAG:Ce luminescent ceramics. The influence of the addition of silver NPs on the sintering kinetics of ceramics was investigated. It was found that the addition of Ag NPs in the concentration range of 0.027–0.44 wt% does not result in the formation of secondary phases in YAG:Ce ceramics. It was demonstrated that the light transmission of ceramics is dependent on the concentration of Ag NPs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…Study of the luminescent properties of the Y 3-х Се х Al 5 O 12 samples for 450 nm excitation (Fig. 5) showed that the luminescence peaks are in the 535-545 nm region, these results being in a good agreement with the references [23][24][25][26]. The nature of the YAG : Ce luminescence spectra is related to electron energy transitions between the degenerate 5d levels of the excited state and two 4f levels of the main state of the Ce 3+ cations [27].…”
Section: Resultssupporting
confidence: 82%
“…Study of the luminescent properties of the Y 3-х Се х Al 5 O 12 samples for 450 nm excitation (Fig. 5) showed that the luminescence peaks are in the 535-545 nm region, these results being in a good agreement with the references [23][24][25][26]. The nature of the YAG : Ce luminescence spectra is related to electron energy transitions between the degenerate 5d levels of the excited state and two 4f levels of the main state of the Ce 3+ cations [27].…”
Section: Resultssupporting
confidence: 82%